2004
DOI: 10.1901/jaba.2004.37-385
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Momentum in Sports: A Partial Replication With Women's Basketball

Abstract: Previous research has applied the behavioral momentum metaphor to men's college basketball. In the current investigation, the relative rate of reinforcement prior to and following adversities (e.g., turnovers, fouls) and periods of time-out were examined in a subset of women's college basketball games.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 4 publications
2
27
0
4
Order By: Relevance
“…Our results provide evidence that offensive and defensive performances were better after than before a timeout. As previously argued, timeouts were effective in decreasing the opponents' local rate of reinforcements and thus the points scored by opponents (Roane et al, 2004). As Mace et al (1992) argued, calling a timeout early in an opponent's scoring streak may avoid the accumulation of ''unanswered points''.…”
Section: Discussionmentioning
confidence: 94%
“…Our results provide evidence that offensive and defensive performances were better after than before a timeout. As previously argued, timeouts were effective in decreasing the opponents' local rate of reinforcements and thus the points scored by opponents (Roane et al, 2004). As Mace et al (1992) argued, calling a timeout early in an opponent's scoring streak may avoid the accumulation of ''unanswered points''.…”
Section: Discussionmentioning
confidence: 94%
“…Vollmer and Bourret (2000), Romanowich, Bourret, and Vollmer (2007), and Alferink, Critchfield, Hitt, and Higgins (2009) demonstrated that the matching law could be used to accurately describe basketball players shot selection, and Seniuk, Williams, Reed, and Wright (2015) extended these findings to describe shot selection of professional hockey players. Furthermore, Roane, Kelley, Trosclair, and Hauer (2004) used behavioral momentum theory to describe patterns of behavior in women's college basketball. Although this line of research is providing an exciting direction for behavior analysts, it does not evaluate interventions but rather provides descriptions of behavior analytic principles applied to sports; therefore, we did not include such articles in our review (for an in-depth review of quantitative analytic techniques as they are applied to sports, see Reed, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These can be managed freely by the coach and depending on the sports, can be requested by a determined number of timeouts, with a duration established by the sports regulation (Gómez et al, 2011;Mace et al, 1992;2004, Wang et al, 2010.…”
Section: Introductionmentioning
confidence: 99%